The role of educational technologies in linking Saudi male and female campuses - Al Lily, A; Abdulrahman Essa A Al Lily (2012)
This empirical study examines the role of educational technologies in connecting male and female university campuses in Saudi Arabia. In order to do so, it addresses the research question: What are the outcomes, ramifications and implications of the ways in which educational technologies have been employed to reconfigure social relations between male and female campuses in Saudi Arabia? This question is answered by a naturalistic study of a state university in the Eastern Province of Saudi Arabia, based on analysis of interviews, observations and documents. From an analysis of the data following the guidelines of the grounded theory technique, two themes emerged: (a) the influence of social relations on the way educational technologies are developed and used, so as to sustain certain aspects of the social structure; (b) the reciprocal influence of the technologies so developed and used on other aspects of the social structure. Considering both themes leads to a theoretical proposition that educational technologies might be introduced to preserve particular components of the social configuration, although once introduced, these technologies might impinge in return upon other components of the social configuration.